An evolutionary approach for the synthesis of fractional potentials - Jesus, Isabel S. (2008)
The problem of point multipoles with electrical charges and the corre- sponding potential is an important subject in the field of electromagnetism. In this work, it is applied the concept of fractional calculus to define, and to evaluate, the electrical potential of fractional order based in a genetic algorithm (GA) optimization scheme.